A new strategy to reconstruct type III acetabular bone defect associated with inflammatory pseudotumor: combined medial and lateral acetabular bone grafting. Issue 50 (December 2017) - Wang, Jing; Wang, Dejiu; Du, Jiang; Lin, Zhen
Abstract: Rationale: Inflammatory pseudotumor has been commonly reported in patients undergoing total hip arthroplasty (THA). Patient concerns: We reported a patient who had a massive intra-pelvic pseudotumour and acetabular bone defect underwent two-stage revision THA. Diagnoses: A new surgical strategy for pseudotumor after THA is performed. Interventions: Thorough debridement intra-pelvic pseudotumour via Smith-Petersen approach, bone grafting on iliac medial surface and plate-screw internal fixation were performed in the first stage, followed by revision of the loosened prosthesis to a cementless primary prosthesis in the second stage. Outcomes: A follow-up for 5 years showed satisfactory recovery of function. Lessons: This surgical revision is less invasive than conventional methods, resulting in a stable and well-functioning hip joint after mid-term follow-up for 5 years.